Elliptical Constructions of Advertisements Displayed on National Geographic Magazine - Satyawan Anshary; Riski Lestiono (Universitas Muhammadiyah Malang, 2020)
Proper use of grammar is paramount as it affects the communication process between the addresser and the addressee. Ellipsis is one of the sub-topics in linguistics that focuses on the effective use of language in any type of discourse. To put it simply, ellipsis refers to the process of omitting/ellipting word(s) in any textual unit when the context is already established and can be assumed. This research is aimed at investigating: (1) the types of elliptical constructions found in advertisements of National Geographic Magazine and (2) the formulations of elliptical constructions in advertisements of National Geographic Magazine. A qualitative content analysis design was employed, taking all the advertisements found throughout the three issues of National Geographic Magazine from January to March 2018 as the research objects. All of the data were examined through the following steps: expert validation, identification, classification, and the elliptical operation analysis utilizing the concept of presupposition. The current study has revealed that all the three types of incohesive ellipsis were employed in the printed advertisements selected as the source material of this study. These three incohesive ellipsis types were: structural, situational, and textual, which are respectively 21, 18, and 6 data in total. These findings were associated heavily on the type of discourse used, the block-style language of printed advertisement is meant to be catchy, short, and effective for the readers upon delivering its information. This current study has come to its conclusion that ellipsis has colored the sentence formulations of advertisement in which economy contributes to its distinct features compared to other existing discourses.